Ventral rectopexy with biological mesh for recurrent disorders of the posterior pelvic organ compartment - Brunner, Michaela; Roth, H.; Günther, K.; Grützmann, Robert; Matzel, Klaus E. (International Journal of Colorectal Disease, 2019)
PURPOSE: Recurrent prolapse of the posterior pelvic organ compartment presents a management challenge, with the best surgical procedure remaining unclear. We present functional outcome and patient satisfaction after laparoscopic and robotic ventral mesh rectopexy (VMR) with biological mesh in patients with recurrence. METHODS: We analyzed data from 30 patients with recurrent posterior pelvic organ prolapse who underwent VMR with biological mesh from August 2012 to January 2018. Data included patient demographics and intra- and postoperative findings; functional outcome as assessed by Cleveland Clinic Constipation Score (CCCS), Obstructed Defecation Score Longo (ODS), and Cleveland Clinic Incontinence Score (CCIS); and patient satisfaction. RESULTS: CCCS, CCIS, and ODS were significantly improved at 6-12 months postoperatively and at last follow-up. Patient satisfaction (visual analog scale [VAS] 6.7 [0 to 10]), subjective symptoms (+ 3.4 [scale - 5 to + 5]), and quality of life improvement (+ 3.0 [scale from - 5 to + 5]) were high at last follow-up. The rates of morbidity and major complications were 13% and 3%, respectively. There were no mesh-related complications or deaths. Difference in type of previous surgery (abdominal or transanal/perineal) had no significant effect on results. CONCLUSIONS: VMR with biological mesh is a safe and effective option for patients with recurrent posterior pelvic organ prolapse. It reduces functional symptoms, has a low complication rate, and promotes patient satisfaction.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Biological mesh; Functional outcome; Laparoscopic ventral rectopexy; Recurrent posterior compartment prolapse; Recurrent rectal prolapse